Characteristics of X-rays produced via laser Compton scattering using quasi-monoenergetic electron beam driven by laser-plasma acceleration. (March 2016) - Miura, Eisuke; Kuroda, Ryunosuke; Toyokawa, Hiroyuki
Abstract: X-ray generation via laser Compton scattering has been demonstrated using a quasi-monoenergetic electron beam with a narrow energy spread driven by laser-plasma acceleration. A well-collimated X-ray beam with a divergence angle of approximately 5 mrad is produced. The X-ray photon number is estimated to be 2 x 10 7 per pulse. The peak energy of the X-rays is estimated to be 60 keV by a numerical simulation.